Circuits of visibility : gender and transnational media cultures - Hegde, Radha Sarma, 1953- (Critical cultural communication., 2011)
Circuits of Visibility explores transnational media environments as pathways to understand the gendered constructions and contradictions that underwrite globalization. Tracking the ways in which gendered subjects are produced and defined in transnationally networked, media saturated environments, Circuits of Visibility presents sixteen essays that collectively advance a discussion about sexual politics, media, technology, and globalization. Covering the internet, television, books, telecommunications, newspapers, and activist media work, the volume directs focused attention to the ways in which gender and sexuality issues are constructed and mobilized across the globe. Contributors' essays span diverse global sites from Myanmar and Morocco to the Balkans, France, U.S., and China, and cover an extensive terrain from consumption, aesthetics and whiteness to masculinity, transnational labor, and cultural citizenship. Circuits of Visibility initiates a necessary conversation and political critique about the mediated global terrain on which sexuality is defined, performed, regulated, made visible, and experienced"--Provided by publisher.